Carvedilol reduces mitochondrial damage induced by hypoxanthine/xanthine oxidase - Oliveira, Paulo (2001)
Abstract The cardioprotective properties of new pharmaceuticals such as carvedilol might be explained by enhanced mitochondrial protection. The aim of this work was to determine the role of carvedilol in the protection of heart mitochondria from oxidative damage induced by hypoxanthine/xanthine oxidase, a known source of oxidative stress in the vascular system. Carvedilol reduced oxidative-stress-induced mitochondrial injury, as seen by the delay in the loss of the mitochondrial transmembranar potential (??), the decrease in mitochondrial swelling, and the increase in mitochondrial calcium uptake. Carvedilol improved the mitochondrial respiratory activity in state III and offered an overall protection in the respiratory control and in the P/O ratios in mitochondria under oxidative stress. The data indicated that carvedilol was able to partly protect heart mitochondria from oxidative stress-induced damage. Our results suggest that mitochondria can be important targets for some cardioprotective pharmaceuticals.